Electrochemical device
By adding zinc salts and calcium salts of bis(perfluoroalkylsulfonyl)imide groups and perfluoroalkylsulfonic acid groups to the electrolyte of lithium-ion batteries, a stable SEI layer was formed, and the surface and body of silicon negative electrode were solved. Phase stability issues improve the service life and electrochemical performance of the battery.
Patent Information
- Application Number
- CN202411362216.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-13
AI Technical Summary
Silicon anions formed during the lithiation of lithium-ion battery anions, as the negative electrode material of lithium-ion battery, highly react with the binder and electrolyte, resulting in an unstable SEI layer, limiting the service life of the silicon anodes and battery performance.
Introduce zinc and calcium salts of bis(perfluoroalkylsulfonyl)imide groups and perfluoroalkylsulfonic acid groups into the electrolyte of the electrochemical device to form a more stable and dense SEI layer to protect the silicon particles from Effects of side reactions of electrolyte.
It significantly improves the surface and bulk phase stability of the silicon negative electrode, reduces side reactions, and extends the service life and electrochemical performance of the battery, including cycle life, Coulomb efficiency and thermal stability.
Smart Images

Figure CN119133572A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to an electrochemical device. Background Art
[0002] Silicon, as the next generation of lithium-ion battery anode material, has attracted much attention due to its higher capacity compared to commercial graphite. However, the silicon anions formed during the lithiation process are highly reactive with the binder and electrolyte components to produce an unstable SEI layer, which limits the service life of the silicon anode, resulting in a shortened battery life and performance degradation. How to solve the surface and bulk stability problems of the silicon anode and improve the battery life and electrochemical performance is an urgent problem to be solved. Summary of the invention
[0003] The object of the present invention is to overcome the above-mentioned problems existing in the prior art and provide an electrochemical device, which introduces zinc salts and calcium salts of bis(perfluoroalkylsulfonyl)imide and perfluoroalkylsulfonic acid groups into the electrolyte of the electrochemical device containing a silicon negative electrode to improve the surface and bulk stability of the silicon negative electrode, thereby improving the service life and electrochemical performance of the battery.
[0004] In order to achieve the above-mentioned object, the present invention provides an electrochemical device, which comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode paste layer located on at least one side of the negative electrode current collector, wherein the negative electrode paste layer comprises a negative electrode active substance, wherein the negative electrode active substance comprises a silicon-based material, and wherein the electrolyte comprises a first additive, wherein the first additive contains Zn and Ca, wherein the Zn and Ca are derived from substance A and substance B, wherein the substance A comprises bis[bis(perfluoroalkylsulfonyl)imide]zinc and / or bis[bis(perfluoroalkylsulfonyl)imide]calcium, and the substance B comprises zinc perfluoroalkyl sulfonate and / or calcium perfluoroalkyl sulfonate.
[0005] The present invention adopts the above technical solution to achieve the following beneficial effects:
[0006] The present invention adds zinc salt and calcium salt of di[bis(perfluoroalkylsulfonyl)imide] group and perfluoroalkylsulfonic acid group as the first additive in the electrolyte, wherein the calcium ions and zinc ions are conducive to forming a more stable and denser SEI layer on the silicon particles, thereby protecting the silicon particles from the side reactions of the electrolyte.
[0007] Moreover, the presence of the first additive significantly improves the surface and bulk stability of the silicon negative electrode, reduces the side reactions of the silicon negative electrode, forms a more stable SEI layer, and improves the thermodynamic stability of the silicon negative electrode, thereby improving the service life and electrochemical performance of the battery, such as improving the cycle life, coulombic efficiency and thermal stability of the battery.
[0008] The endpoints and any values of the range disclosed in this article are not limited to the precise range or value, and these ranges or values should be understood as values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Herein, in the absence of special instructions, data ranges include endpoints. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 This is a SEM image of the surface of the negative electrode sheet of the battery prepared in Example 1 after cycling.
[0010] Figure 2 This is a SEM image of the surface of the negative electrode sheet of the battery prepared in Comparative Example 1 after cycling.
[0011] Figure 3 This is the EDS image of the negative electrode paste layer after the battery prepared in Example 1 was cycled. DETAILED DESCRIPTION
[0012] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0013] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention relates.
[0014] The present invention provides an electrochemical device, the electrochemical device comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, the negative electrode sheet comprising a negative electrode current collector and a negative electrode paste layer located on at least one side of the negative electrode current collector, the negative electrode paste layer comprising a negative electrode active material, the negative electrode active material comprising a silicon-based material, the electrolyte comprising a first additive, the first additive comprising Zn and Ca, Zn and Ca coming from substance A and substance B, the substance A comprising zinc di[bis(perfluoroalkylsulfonyl)imide] and / or calcium di[bis(perfluoroalkylsulfonyl)imide], the substance B comprising zinc perfluoroalkyl sulfonate and / or calcium perfluoroalkyl sulfonate. The present invention forms a stable SEI by introducing a mixed multivalent first additive, improves the surface and bulk stability of the silicon negative electrode, is conducive to improving the thermodynamic stability of the silicon negative electrode, can also reduce side reactions, and improve battery performance.
[0015] In some embodiments, the perfluoroalkyl group in substance A and substance B is selected from at least one of trifluoromethyl, pentafluoroethyl and heptafluoroisopropyl.
[0016] In some embodiments, substance A includes zinc bis(trifluoromethylsulfonyl)imide (Zn(NTf2)2) and / or calcium bis(trifluoromethylsulfonyl)imide (Ca(NTf2)2).
[0017] In some embodiments, substance B includes zinc trifluoromethanesulfonate (Zn(OTf)2) and / or calcium trifluoromethanesulfonate (Ca(OTf)2).
[0018] In some embodiments, the amount of the first additive added to the electrolyte is A mol / L, and A is 0.05-0.15, such as 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15. When the concentration of the additive is within this range, the side reactions of the silicon negative electrode can be further reduced, a more uniform and stable SEI layer can be formed, and the cycle life, coulomb efficiency and thermal stability of the battery can be improved, while maintaining a low internal resistance. If the concentration of the first additive is too high, an excessively thick SEI layer will be formed on the surface of the electrode, hindering the transmission of lithium ions, increasing the internal resistance of the battery, and resulting in a decrease in the charge and discharge efficiency of the battery; if the concentration is too low, the effect of the additive cannot be fully exerted, and an effective and stable SEI layer cannot be formed, resulting in an uneven SEI layer, which in turn affects the cycle life and safety of the battery.
[0019] In some embodiments, A is 0.08-0.12.
[0020] In some embodiments, in terms of molar amount, the ratio of the amount of substance A to substance B added in the electrolyte is 1:1-9, such as 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9. When the amount ratio of substance A to substance B in the additive is within this range, the side reaction of the silicon negative electrode can be further reduced, a more uniform and stable SEI layer can be formed, and the cycle life, coulomb efficiency and thermal stability of the battery can be improved, while maintaining a low internal resistance. If the ratio deviates from this range, the SEI quality will be reduced, and the cycle and safety performance of the battery will be reduced.
[0021] In some embodiments, the ratio of the amount of substance A to that of substance B added to the electrolyte is 1:1-5 on a molar basis.
[0022] In some embodiments, in terms of molar amount, the ratio of the amount of Zn to Ca added in the electrolyte is 1:1-9, such as 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9. When the ratio of the amount of Zn to Ca added is within this range, the side reaction of the silicon negative electrode can be further reduced, a more uniform and stable SEI layer can be formed, and the cycle life, coulomb efficiency and thermal stability of the battery can be improved while maintaining a low internal resistance. If the ratio deviates from this range, the SEI quality will be reduced, and the cycle and safety performance of the battery will be reduced.
[0023] In some embodiments, the electrolyte further includes a lithium salt.
[0024] In some embodiments, the lithium salt includes but is not limited to at least one of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium perchlorate (LiClO4), lithium trifluoromethylsulfonate (LiCF3SO3), lithium difluorophosphate (LiPO2F2), lithium tetrafluoroborate (LiBF4), lithium difluorooxalatoborate (LiDFOB) and lithium dioxalatoborate (LiBOB).
[0025] In some embodiments, the content of lithium salt in the electrolyte is 10 wt%-20 wt%, for example, 10 wt%, 12 wt%, 14 wt%, 16 wt%, 18 wt% or 20 wt%.
[0026] In some embodiments, the electrolyte further includes an aprotic organic solvent.
[0027] In some embodiments, the aprotic organic solvent includes but is not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), methyl propyl carbonate (MPC), butylene carbonate (BC), ethyl acetate (EA), ethyl propionate (EP), n-propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), sulfolane (SL), dimethyl sulfone (MSM), dioxolane (DOL) and ethylene glycol dimethyl ether (DME).
[0028] In some embodiments, the content of the aprotic organic solvent in the electrolyte is 50 wt %-80 wt %, for example, 50 wt %, 60 wt %, 70 wt % or 80 wt %.
[0029] In some embodiments, the electrolyte may further include functional additives, such as but not limited to 1,3-propane sultone (PS), 1,3-propylene sultone (PST), vinyl sulfate (DTD), vinyl disulfate (BiDTD), methylene disulfonate (MMDS), trimethylsilyl methane sulfonate, dimethyl methylene sulfonate, 4-acetylphenyl trifluoromethanesulfonate, phenyl trifluoromethanesulfonate, 6-quinolyl trifluoromethanesulfonate, N-ethyl-5-phenylisoxazole-3'-sulfonate, fluoroethylene carbonate (FEC), fluoropropylene carbonate, fluoroethyl acetate, fluoropropyl acetate, fluorodimethyl carbonate and fluorodiethyl carbonate.
[0030] In some embodiments, the content of the functional additive in the electrolyte is 5wt%-15wt%, for example, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt% or 15wt%.
[0031] In some embodiments, the negative electrode current collector may be copper foil or a composite current collector.
[0032] In some embodiments, the silicon-based material includes silicon-carbon material, nano-silicon and silicon-oxygen material (SiO x , 0<x<2).
[0033] In some embodiments, the mass content of silicon in the negative electrode paste layer is B wt %, where B is 5-50.
[0034] In some embodiments, B is 10-20.
[0035] In the present invention, when determining the content of elements in the negative electrode paste layer, the content in the paste powder after removing the negative electrode current collector from the negative electrode sheet is used as the content, which can be specifically determined by an energy dispersive spectrometer (EDS).
[0036] In some embodiments, the BET specific surface area of the silicon-based material is C m 2 / g, C is 1-5, such as 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5. When the specific surface area of the silicon-based material is within this range, it is beneficial to improve the uniformity of the formed SEI layer, improve the liquid storage performance of the silicon negative electrode, and thus improve the performance of the battery.
[0037] In the present invention, the BET specific surface area of the material can be determined by nitrogen adsorption experiment combined with BJH (Barrett-Joyner-Halenda) method. Specifically, the sample pretreatment conditions are: temperature 150°C-200°C, time 6-12h, vacuum degree <10 -5Torr; nitrogen adsorption experimental conditions: adsorption gas is nitrogen, temperature is 77K (liquid nitrogen temperature), pressure is 0.01 to 1.0 relative pressure (P / Po), number of adsorption isotherm points: 30 to 50 points, covering low pressure to high pressure area. BET specific surface area is obtained by linear fitting in the relative pressure range of 0.05 to 0.3.
[0038] In some embodiments, C is 1.5-2.
[0039] In some embodiments, the particle size Dv50 of the silicon-based material is 5 μm-50 μm, such as 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, and 50 μm.
[0040] In some embodiments, the particle size Dv50 of the silicon-based material is 10 μm-20 μm.
[0041] In the present invention, the particle size Dv50 of the material can be measured by a particle size analyzer.
[0042] In some embodiments, the aspect ratio of the silicon-based material is 1-5, such as 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5. When the aspect ratio of the silicon-based material is within this range, it is beneficial to improve the uniformity of the formed SEI layer, improve the liquid storage performance of the silicon negative electrode, and thus improve the performance of the battery. If it is too large, the rigidity of the formed SEI layer will decrease, and it will be easy to break, resulting in a decrease in the cycle performance of the battery.
[0043] In some embodiments, the aspect ratio of the silicon-based material is 1-2.
[0044] In the present invention, the aspect ratio refers to the ratio of the length to the width of the silicon-based material, the length refers to the longest particle diameter, and the width refers to the shortest particle diameter perpendicular to the length direction.
[0045] In some embodiments, the electrochemical device satisfies 0.25≤A*B*C≤20, such as 0.25, 0.5, 1, 1.5, 2, 3, 4, 5, 6, 7, 8, 9, 10, 12, 14, 16, 18, 20. When the particle size and specific surface area of the silicon-based material and the content of the first additive satisfy this relationship, it is beneficial to improve the uniformity and density of the formed SEI layer, reduce the occurrence of side reactions, and improve the liquid storage performance of the silicon negative electrode, thereby improving the performance of the battery.
[0046] In some embodiments, the content of Zn element in the negative electrode paste layer is 0.001-0.1 wt %, and the content of Ca element is 0.01-0.1 wt %.
[0047] In some embodiments, the content of Zn element in the negative electrode paste layer is 0.005-0.08 wt %, and the content of Ca element is 0.01-0.08 wt %.
[0048] In some embodiments, the total content of Zn element and Ca element in the negative electrode paste layer is 0.01-0.2 wt %.
[0049] When the particle size Dv50 of the silicon-based material is 5μm-50μm, the aspect ratio is 1-5, and the total content of Zn and Ca elements in the negative electrode sheet is 0.01-0.2wt%, a suitable SEI film thickness can be formed, which promotes the uniformity of the SEI film, improves the liquid storage performance of the silicon negative electrode while inhibiting the expansion of silicon, and synergistically improves the battery's kinetic performance.
[0050] In some embodiments, the negative electrode active material further includes a carbon-based material (including but not limited to at least one of natural graphite, artificial graphite, mesophase carbon microbeads, hard carbon, soft carbon, etc.).
[0051] In some embodiments, the negative electrode paste layer contains 70wt%-98wt% (for example, 70wt%, 80wt%, 90wt%, 95wt% or 98wt%) of the negative electrode active material, 0.5wt%-15wt% (for example, 0.5wt%, 1wt%, 5wt%, 10wt% or 15wt%) of the conductive agent and 0.5wt%-15wt% (for example, 0.5wt%, 1wt%, 5wt%, 10wt% or 15wt%) of the binder.
[0052] In some embodiments, the conductive agent includes, but is not limited to, at least one of conductive carbon black, carbon nanotubes, carbon fibers, and Ketjen black.
[0053] In some embodiments, the binder includes but is not limited to at least one of polyvinylidene fluoride (PVDF), styrene-butadiene rubber emulsion, polytetrafluoroethylene emulsion, sodium carboxymethyl cellulose, sodium alginate, polyvinyl alcohol, polyacrylic acid, lithium polyacrylate, sodium polyacrylate and carboxylated chitosan.
[0054] In some embodiments, the positive electrode sheet includes a positive electrode paste layer, and the positive electrode paste layer includes a positive electrode active material, a binder and a conductive agent. The types of the binder and the conductive agent can refer to the description in the negative electrode paste layer, and their types can be the same as or different from those in the negative electrode paste layer.
[0055] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode paste layer located on the positive electrode current collector.
[0056] In some embodiments, the electrochemical device satisfies 10≤D+150A≤30 (for example, it can be 10, 15, 20, 25, 30), wherein D is the content of the conductive agent in the positive electrode paste layer, in units of wt%. When the content of the first additive and the conductive agent satisfies this relationship, on the one hand, the positive electrode capacity can be increased, thereby increasing the energy density of the battery; on the other hand, the first additive improves the surface and bulk stability of the silicon negative electrode, so that the silicon negative electrode maintains a long-term stable lithium insertion and extraction rate, and the addition of the conductive agent can improve the structure of the positive electrode, enhance its stability during the charge and discharge process, and promote the electrochemical reaction between the positive electrode active material and the electrolyte, thereby increasing the energy density and efficiency of the battery and extending the service life of the battery; when the content of the first additive and the conductive agent satisfies this relationship, the lithium insertion and extraction rates of the positive and negative electrodes can be matched, and the consistency of the structure of the positive and negative electrodes during the battery cycle can be maintained, and the lithium insertion and extraction rates of the two electrodes will not be inconsistent due to the instability of one of the electrode structures, thereby improving the charge and discharge performance of the battery, improving the energy density and efficiency of the battery, and extending the service life of the battery.
[0057] In some embodiments, D is 0.1-25 (for example, 0.1, 1, 5, 10, 15, 20, 25), preferably 1-10.
[0058] In some embodiments, the positive electrode paste layer includes 60wt%-98wt% (for example, 60wt%, 70wt%, 80wt%, 90wt%, 95wt% or 98wt%) of the positive electrode active material, 0.1wt%-25wt% (for example, 0.1wt%, 1wt%, 5wt%, 10wt%, 15wt%, 20wt% or 25wt%) of the conductive agent and 0.9wt%-15wt% (for example, 0.9wt%, 1wt%, 5wt%, 10wt% or 15wt%) of the binder.
[0059] In some embodiments, the positive electrode active material includes a lithium composite oxide.
[0060] In some embodiments, the chemical formula of the lithium composite oxide is Li (1+x) Ni y Co z M (1-y-z)O2; where -0.1≤x≤1 (e.g., -0.1, 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1), 0≤y≤1 (e.g., 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1), 0<z≤1 (e.g., 0.1, 0.2, 0 .3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1), and 0<y+z≤1 (for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1); M is at least one of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo and Zr.
[0061] In some embodiments, the positive electrode active material is lithium cobalt oxide.
[0062] The separator may be a conventional microporous membrane in the art. In some embodiments, the separator includes a substrate layer, and the material of the substrate layer includes at least one of polyethylene (PE) and polypropylene (PP). The separator may also contain other coatings located on at least one surface of the substrate, such as an inorganic coating, a rubber coating layer, etc.
[0063] In some embodiments, the inorganic coating comprises 80-99wt% inorganic particles and 1-20wt% adhesive. The inorganic particles may include at least one of aluminum oxide, magnesium oxide, boehmite, barium sulfate, barium titanate, zinc oxide, calcium oxide, silicon dioxide, silicon carbide, and nickel oxide. The adhesive may include at least one of polyacrylate, polytetrafluoroethylene, polyvinylidene fluoride, hexafluoropropylene-vinylidene fluoride copolymer (for example, polyvinylidene fluoride-hexafluoropropylene copolymer), polyimide, polyacrylonitrile, and polymethyl methacrylate.
[0064] In some embodiments, the coating layer comprises at least one of styrene, vinyl chloride, perfluoropropylene, chlorotrifluoroethylene, tetrafluoroethylene, vinylidene chloride, tetrachloroethylene, acrylate (for example, methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate), methacrylic acid, methacrylate (for example, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate), and acrylonitrile.
[0065] If not otherwise specified, other options for the electrochemical device are conventional options in the art, and the assembly method thereof can be performed in a conventional manner in the art.
[0066] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0067] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0068] The present invention is described in detail below in conjunction with specific embodiments, which are used to understand but not to limit the present invention.
[0069] Example 1
[0070] 1) Preparation of positive electrode
[0071] The positive electrode active materials lithium cobalt oxide, polyvinylidene fluoride (PVDF) and conductive carbon black are mixed in a mass ratio of 96:2:2, N-methylpyrrolidone (NMP) is added, and the mixture is stirred under the action of a vacuum mixer until the mixed system becomes a positive electrode active slurry with uniform fluidity; the positive electrode active slurry is evenly coated on both surfaces of a 10 μm thick aluminum foil; the coated aluminum foil is placed in an oven at 60°C and dried for 24 hours, and then rolled and cut to obtain the desired positive electrode sheet.
[0072] 2) Negative electrode preparation
[0073] Silicon-carbon material, artificial graphite, conductive carbon black (SP) and styrene-butadiene rubber (SBR) were mixed in a mass ratio of 2:6:1:1, deionized water was added, and negative electrode active slurry was obtained under the action of a vacuum mixer; the negative electrode active slurry was evenly coated on both surfaces of a 8 μm thick copper foil; the coated copper foil was dried at room temperature, then transferred to a 60°C oven for drying for 24 hours, and then cold pressed and cut to obtain a negative electrode sheet. The BET specific surface area of the silicon-carbon material is C m 2 / g, C is 1.8; particle size Dv50 is 15μm, and aspect ratio is 1.5.
[0074] 3) Preparation of electrolyte
[0075] In a glove box filled with argon (H2O<0.1ppm, O2<0.1ppm), EC / DMC was mixed evenly in a volume ratio of 1:1, and then fully dried lithium hexafluorophosphate (LiPF6) was quickly added thereto to form a concentration of 1 mol / L, and then 3wt% of fluoroethylene carbonate (FEC) was added and dissolved, and the first additive (final concentration was A mol / L, A=0.1) was added, and the electrolyte was prepared after mixing evenly. The first additive in the electrolyte was composed of Zn(NTf2)2 and Ca(OTf)2 (molar ratio was 3:7).
[0076] 4) Preparation of lithium-ion batteries
[0077] The positive electrode sheet of step 1), the negative electrode sheet of step 2) and the separator are stacked in the order of positive electrode sheet, separator and negative electrode sheet, and then wound to obtain a battery cell; the battery cell is placed in an outer packaging aluminum foil, and the electrolyte of step 3) is injected into the outer packaging. After vacuum packaging, standing, formation, shaping, sorting and other processes, a lithium-ion battery is obtained.
[0078] The negative electrode sheet was obtained by disassembling the battery cell, and the negative electrode paste layer powder was scraped off after drying. EDS analysis was performed on it to determine the Si, Zn and Ca contents in the negative electrode paste layer (EDS results in the negative electrode paste layer are shown in Figure 3 ), the results are shown in Table 1, the mass content of silicon in the negative electrode paste layer is B wt%. D is the content of the conductive agent in the positive electrode paste layer, in wt%, as shown in Table 1.
[0079] Comparative Example 1
[0080] The operation is carried out in accordance with the method described in Example 1, except that the first additive is not added to the electrolyte.
[0081] Comparative Example 2
[0082] The operation was carried out in accordance with the method described in Example 1, except that only 0.1 M Zn(NTf2)2 was contained in the first additive, that is, no Ca(OTf)2 was added.
[0083] Comparative Example 3
[0084] The operation was carried out in accordance with the method described in Example 1, except that the first additive contained only 0.1 M Ca(OTf)2, i.e., no Zn(NTf2)2 was added.
[0085] Example 2
[0086] The operation was carried out according to the method described in Example 1, except that the contents of Zn(NTf2)2 and Ca(OTf)2 in the first additive were different, as shown in Table 1.
[0087] Example 3 Group
[0088] The operation was carried out according to the method described in Example 1, except that the silicon content in the silicon-carbon material was different, so that the mass content B of the silicon element in the negative electrode paste layer was different, and the BET specific surface area C and aspect ratio of the silicon-carbon material were also different, as shown in Table 1.
[0089] Example 4 Group
[0090] The operation was carried out according to the method described in Example 1, except that the content D of the conductive carbon black in the positive electrode paste layer was different, as shown in Table 1.
[0091] Example 5 Group
[0092] The operation is performed according to the method described in Example 1, except that at least two of A, B, C and D are different, as shown in Table 1.
[0093] Table 1
[0094] Group A Zn:Ca molar ratio B C Aspect Ratio A*B*C D D+150A Zn content Ca content Example 1 0.1 3:7 15 1.8 1.5 2.7 2 17 0.02% 0.029% Example 2-1 * 1:9 * * * * * * 0.007% 0.037% Example 2-2 * 1:1 * * * * * * 0.033% 0.02% Example 2-3 0.08 3:7 * * * 2.16 * 14 0.016% 0.023% Embodiment 2-4 0.12 3:7 * * * 3.24 * 20 0.024% 0.035% Embodiment 2-5 * 7:3 * * * * * * 0.047% 0.012% Embodiment 2-6 0.01 3:7 * * * 0.27 * 3.5 0.002% 0.003% Embodiment 2-7 0.3 3:7 * * * 8.1 * 47 0.06% 0.086% Example 3-1 * * 10 1.5 1.2 1.5 * * / / Example 3-2 * * 20 2 1.7 4 * * / / Example 3-3 * * 5 1 1.3 0.5 * * / / Embodiment 3-4 * * 40 3 1.5 12 * * / / Example 4-1 * * * * * * 1 16 / / Example 4-2 * * * * * * 10 25 / / Example 4-3 * * * * * * 0.1 15.1 / / Example 4-4 * * * * * * 25 40 / / Example 5-1 0.05 * 15 1.8 * 1.35 0.1 7.6 0.01% 0.015% Example 5-2 0.12 * 45 4 1.5 21.6 * 20 / /
[0095] Note: * indicates the same as in Example 1, / indicates not measured, the molar ratio of Zn to Ca refers to the molar ratio of Zn to Ca in the electrolyte, and the Zn content and Ca content refer to the Zn content and Ca content in the negative electrode paste layer.
[0096] Example 6 and Comparative Example 4
[0097] The operation was carried out according to the method described in Example 1, except that the type of substance used in the first additive was different, as shown in Table 2. 16 N2O8S4Zn is a homologue of Zn(NTf2)2, with -CF3 changed to -CF2CF3; (CF2CF3SO3)2Ca is a homologue of Ca(OTf)2, with -CF3 changed to -CF2CF3.
[0098] Table 2
[0099]
[0100] Test Case
[0101] The performance of the batteries prepared in the examples and comparative examples was tested, and the results are shown in Table 3.
[0102] (1) First efficiency: 25°C constant temperature for 30 min, 1C constant current charging to 4.5 V, 4.5 V constant voltage charging, 0.3C cut-off; 0.7C discharge to 3 V. Calculate the first efficiency = (first discharge capacity / first charge capacity) × 100%.
[0103] (2) Capacity retention rate: 25°C constant temperature for 30 min, 1C constant current charging to 4.5 V, 4.5 V constant voltage charging, 0.3C cut-off; 0.7C discharge to 3 V. Perform 200 charging cycles according to this charging system and calculate the capacity retention rate.
[0104] The negative electrode sheet samples after the cycle test were collected and the surface cracks of the negative electrode sheet were observed by scanning electron microscope (SEM). Figure 1 and Figure 2 The SEM images of the negative electrode surface after battery cycling prepared in Example 1 and Comparative Example 1 are shown respectively. It can be seen from the images that there are multiple obvious cracks of varying sizes on the surface of the negative electrode in Comparative Example 1, while there are basically no cracks on the surface of the negative electrode in Example 1.
[0105] (3) Oven temperature pass rate: fully charged batteries are placed in the test chamber, and the test chamber is heated at a rate of 5°C / min. When the temperature in the chamber reaches 130°C±2°C, the temperature is kept constant for 60 minutes. If no fire occurs, it is judged as passed, and if fire occurs, it is judged as failed. The oven temperature pass rate is expressed as the number of batteries that pass / the total number of batteries tested.
[0106] Table 3
[0107]
[0108]
[0109] It should be noted that, in this article, the terms "comprise", "include" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be pointed out that the scope of the method and device in the embodiment of the present invention is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.
[0110] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. An electrochemical device, characterized in that The electrochemical device comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The negative electrode sheet comprises a negative electrode current collector and a negative electrode paste layer located on at least one side of the negative electrode current collector. The negative electrode paste layer comprises a negative electrode active material. The negative electrode active material comprises a silicon-based material. The electrolyte comprises a first additive. The first additive contains Zn and Ca. Zn and Ca are derived from substance A and substance B. Substance A comprises zinc bis(perfluoroalkylsulfonyl)imide and / or calcium bis(perfluoroalkylsulfonyl)imide, and substance B comprises zinc perfluoroalkyl sulfonate and / or calcium perfluoroalkyl sulfonate.
2. The electrochemical device according to claim 1, characterized in that The perfluoroalkyl group in substance A and substance B is selected from at least one of trifluoromethyl, pentafluoroethyl and heptafluoroisopropyl; and / or The silicon-based material includes at least one of silicon-carbon material, nano-silicon and silicon-oxygen material.
3. The electrochemical device according to claim 1 or 2, characterized in that: The amount of the first additive added to the electrolyte is A mol / L, A is 0.05-0.15, preferably 0.08-0.12; Preferably, in terms of molar amount, the ratio of the amount of substance A to that of substance B added in the electrolyte is 1:1-9; Preferably, in terms of molar amount, the ratio of the added amounts of Zn and Ca in the electrolyte is 1:1-9.
4. The electrochemical device according to any one of claims 1 to 3, characterized in that: The mass content of silicon in the negative electrode paste layer is B wt%, where B is 5-50, preferably 10-20; The BET specific surface area of the silicon-based material is Cm 2 / g, C is 1-5, preferably 1.5-2; The particle size Dv50 of the silicon-based material is 5 μm-50 μm, preferably 10 μm-20 μm; and / or The aspect ratio of the silicon-based material is 1-5, preferably 1-2.
5. The electrochemical device according to claim 4, characterized in that The electrochemical device satisfies 0.25≤A*B*C≤20.
6. The electrochemical device according to any one of claims 1 to 5, characterized in that: The content of Zn element in the negative electrode paste layer is 0.001-0.1wt%, and the content of Ca element is 0.01-0.1wt%; Preferably, the content of Zn element in the negative electrode paste layer is 0.005-0.08 wt %, and the content of Ca element is 0.01-0.08 wt %.
7. The electrochemical device according to any one of claims 1 to 6, characterized in that: The total content of Zn element and Ca element in the negative electrode paste layer is 0.01-0.2 wt %.
8. The electrochemical device according to any one of claims 1 to 7, characterized in that: The positive electrode sheet comprises a positive electrode paste layer, and the positive electrode paste layer comprises a positive electrode active material, a binder and a conductive agent; Preferably, the electrochemical device satisfies 10≤D+150A≤30, wherein D is the content of the conductive agent in the positive electrode paste layer, expressed in wt%.
9. The electrochemical device according to claim 8, characterized in that D is 0.1-25, preferably 1-10.
10. The electrochemical device according to claim 8, characterized in that The positive electrode active material includes a lithium composite oxide; Preferably, the chemical formula of the lithium composite oxide is Li (1+x) Ni y Co z M (1-y-z) O2; Among them, -0.1≤x≤1, 0≤y≤1, 0<z≤1, and 0<y+z≤1; M is at least one of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo and Zr.
Citation Information
Patent Citations
Lithium ion battery non-aqueous electrolyte and lithium ion battery using same
CN114597491A
Electrolyte, battery monomer, preparation method of battery monomer, battery and power utilization device
CN117976970A
Metal negative electrode surface modification method and application thereof
CN117995975A
Electrolyte, battery cell and preparation method therefor, battery, and electric device
WO2024087799A1
